Associated between polymorphism of DRB1 gene with production and composition of milk in Turkish Awassi sheep - ناصر, ميساء احمد; الانباري, نصر نوري (Journal of Kerbala for Agricultural Sciences, 2016)
This study was undertaken at the Ruminants Researches Station (20 km west of Baghdad) pertaining to the Directorate for Agricultural Researches / Ministry of Agriculture, Reproductive laboratory at the College of Agriculture/University of Baghdad as well as Laboratory Bridge Musayyib specialist to technology and bio-analysis and molecular genetics, and analysis of molecular genetics from 01/03/2015 to 15 / 01/2016 .The aim of this study was Relationship of DRB1 polymorphism with production and composition of milk. Affected Daily and total milk production and the percentage of fat in milk was significant (P≤0.05) depending on the different phenotype DRB1 gene, but the length of milk season and other milk components were not significantly affected by different phenotype appearance of the gene . It can be concluded through the study of polymorphism of the gene DRB1 revealed possibility of adopted them in sheep improvement strategy to increased the milk production in the breeding schemes, by selecting and crossing the highly growth lambs genotypes or phenotypes. the best growth of the lambs and attention also to study the application of a larger sample and for several seasons productivity would give more accurate results for the application of exclusion and replacement strategy.